Qualidade e quantidade de águas pluviais escoadas a partir de telhados verdes extensivos em Santa Maria - RS - Pessoa, Jonas Onis (2016)
Green roofs have increasingly become an integral part of urban environments, mainly due to their aesthetic benefits, thermal comfort and efficiency in controlling excess runoff. However, the effects of this emerging technology in the qualitative characteristics of rainwater is still poorly understood. In this study, we evaluated the quality of rain water runoff from two extensive green roofs and a roof built with corrugated fiber cement sheets (control roof) installed in Santa Maria - RS. In addition, we analyzed the performance of both types of roof for controlling storm water runoff. For qualitative analysis of water, were determined physical (turbidity, apparent color, true color, electrical conductivity, total solids, dissolved solids, suspended solids and temperature), chemical (pH, phosphate, total nitrogen, nitrate, nitrite, chloride, sulfates, BOD, and hardness), metal (copper, iron, zinc, lead and chromium) and microbiological parameters (total coliforms and E. coli). Differences in rain water quality obtained at collection points were assessed using parametric test (Test t) and non-parametric tests (Mann-Whitney and Kruskal-Wallis test) with a significance level of 5% probability. The control of storm water runoff was analyzed from the runoff coefficient (C) and the water portion stored in both types of coverage. The results showed that, in general, GRs have not improved water quality, as indicated by some authors. On both green roofs occurred an increase of chloride, electrical conductivity, color, BOD, hardness, total coliforms, E. coli, phosphate, sulfate and turbidity. However, it was observed that GRs are able to convert the slightly acidic rainfall into basic water, which confirms its potential to neutralize acid deposition. Except for a few parameters, the quality of the collected water from the control roof did not differ significantly compared to GRs water. By comparing the results with the Brazilian environmental legislation, we noted that the runoff from all three roofs have potential for non-potable uses, such as floor and sidewalks washing, garden irrigation, toilet flushing, among others. About the performance of roofs in controlling storm water runoff, there was a significant efficiency of green roofs compared to the roof built with corrugated fiber cement sheets. This result was typified by the average values of flow coefficient, about 0.43 for GRs and 0.83 for control roof. However, the efficiency of green roofs controlling runoff proved to be very sensitive to weather conditions and antecedent soil moisture. To a future study about performance and interaction of various factors that could influence green roofs water quality and in its efficiency and controlling storm water runoff, we suggest long-term studies with different types of substrates, plant species and installation of the structures in locations with other types of occupation and environmental conditions, different from those verified in this work.